ACTUAL PROBLEMS OF DATA MINING AND DIGITAL ECONOMY - Anatoly Alekseevich Moskvitin; Aleksandr Viktorovich Bokov (Современная наука и инновации)
This work is a review article on the materials of the International scientific and practical conference "data Mining and digital economy", held from 22 to 24 November 2018 in Pyatigorsk branch of the State university of economics ("Plekhanov Russian University of Economics" in Pyatigorsk, Stavropol territory) with the financial support of the Russian Foundation for basic research (Project № 18-0120095).